AB0415 SERUM RESISTIN LEVEL IN SYSTEMIC LUPUS ERYTHEMATOSUS: RELATION TO LUPUS NEPHRITIS AND DISEASE ACTIVITY. (2nd June 2020) - Ismail, F.; Salah, S.; Abdelhamed, M.; Aboel Ela, M.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease affecting different organs and systems.. Adipokines have recently been implicated as mediators of immune and inflammatory processes. Human resistin is a cytokine that induces low-grade inflammation by stimulating monocytes Objectives: The aim of this work is to assess the serum level of resistin in SLE patients and to detect its relation to lupus nephritis, and disease activity Methods: 40 patients with SLE with age ranged between 18-48 years and 20 healthy age, sex and BMI matched volunteer were enrolled in this study. According to the presence or absence of lupus nephritis (LN), patients were classified into two subgroups Full history, clinical examination and laboratory investigations were performed for all patients including serum resistin level Results: The level of serum resistin was higher in SLE patients than the controls (p=0.001). Also, serum resistin levels were higher in patients with lupus nephritis than those without nephritis (p= 0.02). Serum resistin level correlated positively with the levels of ESR (p< 0.001 ), CRP (p= 0.005), Anti-dsDNA (p= 0.002 ) and serum urea (p= 0.002). Serum resistin levels correlated negatively with hemoglobin levels (p= 0.001 ) and levels of C3 (p< 0.001 ) and C4 (p< 0.001). There was a significant positive correlation between serum resistin level and the presence of albumin (p= 0.001), RBCs (p= 0.003), pus cells (p= 0.001 ) and casts (p< 0.001 ) in urine and also with the levels of 24 hour urinary protein and protein/ creatinine ratio (p<0.001). Serum resistin level was found to be strongly correlated with SLEDAI (p< 0.001). No correlation was found between serum resistin levels and ISN/RPS classification of renal biopsy. Conclusion: Serum resisitin level can be used as a marker of inflammation, nephritis, disease activity in patients with SLE. Disclosure of Interests: None declared